Pengaruh Lama Penyimpanan Terhadap Nilai pH Dadih Fortifikasi Vitamin D3 - Ayu Meilina; Yunita Nazarena; Yuli Hartati (Jurnal Sehat Mandiri, 2022)
Research on 504 women aged 18-40 years found the average serum concentration of 25(OH)D was 48 nmol/L with the incidence of vitamin D deficiency as much as 63%. Vitamin D deficiency is associated with several metabolic diseases. This incident can be controlled with fortification of vitamin D which is usually given to dairy products and their processed products. Dadih is the result of spontaneously fermenting buffalo milk at a temperature of 28°-32°C for 24-48 hours in a bamboo tube. pH is an important factor that affects the survival of lactic acid bacteria found in fermented products. Decrease in pH along with an increase in total acid. The higher the total acid, the lower the pH of Dadih. This study aims to test the stability of the pH value of Dadih during storage at cold temperatures for 28 days. This study used an experimental study with five treatments repeated duplo. Measurement of the pH value of Dadih using the standard method used by PT. Saraswati Indo Genetech with No. Instructions SNI 01-2891-1992 point 16. Analysis showed that the pH value of Dadih fortified vitamin D3 in cold storage remained stable for 28 days. In conclusion, there was no damage to Dadih fortified vitamin D3, so it was safe for consumption. Future research is expected to measure the effectiveness of fortified vitamin D3 in Dadih.